Types and Forms of Audiovisual Translation and Their Roles in the Translation Process - Bozorova , Vasila Ilkhomovna (The Lingua Spectrum, 2026)
Audiovisual translation (AVT) refers to a broad set of techniques used to make audiovisual products understandable and accessible to multilingual and multicultural audiences. This paper deals with the issues related to investigating the principal forms of AVT, including dubbing, voice-over, subtitling, localization, adaptation, and summary translation, emphasizing their role within the translation process. Each form of AVT is shaped by specific linguistic, cultural, and technical constraints that influence translators’ decisions. Issues such as time and space limitations, synchronization between sound and image, cultural references, audience expectations, and technological standards are central to the quality of the final product. The abstract also underlines that AVT is not a purely linguistic activity but a multimodal practice requiring close interaction between language, visuals, and sound. By analyzing these interconnected factors, the study argues that successful audiovisual translation depends on a holistic approach that carefully balances accuracy, clarity, and cultural appropriateness to ensure effective communication and audience engagement.